Correction: SARS-CoV-2 infection in China-Before the pandemic. - Huiying Liang; Lingling Zheng; Huimin Xia; Jinling Tang (PLoS Neglected Tropical Diseases, 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0008472.].